INVENTARISASI JAMUR MAKROSKOPIS PADA HABITAT RAWA GAMBUT Di KAWASAN CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG KALIMANTAN BARAT - Prayogo, Ogi; Rahmawati, Rahmawati; Mukarlina, Mukarlina (Universitas Tanjungpura, 2019)
This inventory needs to be carried out to determine the types of macroscopic fungi that are found in the Peat Swamp Habitat of the Cabang Panti Gunung Palung National Park. Taking mushroom samples using the Purposive sampling method and roaming method by tracing the path. Identification is carried out based on macroscopic characters. Based on the results of the inventory at the Cabang Panti of Gunung Palung National Park, there were 3 macroscopic fungi from the Order of Agaricales, Auriculariales and Polyporales which which has three species including Auricularia auricula, auricularia delicata, Lichenomphalia sp. and Microporus xanthopus.